PENGEMBANGAN SISTEM SELEKSI PRAJURIT TNI AL KORPS ELEKTRONIKA BERBASIS KUALIFIKASI, KOMPETENSI DAN KINERJA DALAM PENENTUAN KOMPENSASI SEBAGAI PENGAWAK PERTAMA ALUTSISTA KRI - Wahid, Nur Rizal Abdul; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to develop a selection system for Indonesian Navy (TNI AL) personnel in the Electronics Corps based on qualifications, competencies, and performance as criteria for determining compensation for primary crew members of modern warship. Conventional selection processes often lack integration of comprehensive assessment methods that objectively evaluate educational background, technical skills, and performance records. Employing a mixed method approach, this research combines quantitative analysis of personnel performance data with qualitative interviews and field observations. The developed selection model uses weighted multicriteria analysis to create a transparent, accountable, and adaptive assessment tool aligned with advancements in naval technology. Findings indicate that the integrated selection system enhances the effectiveness of personnel placement, reduces subjective biases in decision-making, and establishes a fairer basis for compensation tied to actual contributions and performance. The proposed system is expected to serve as a reference for human resource management policies within the Indonesian Navy, supporting the optimal operation of warship.